Design and Build Smart Street Lights by Utilizing Sensor and Tranduser Technology Based on Arduino Uno - Marthin Martunas Sihotang; Iqbal Kamil Siregar; Rika Nofitri (Universitas Budi Darma, 2022)
Street lights or also known as Public Street Lighting (PJU) are lights that are used for street lighting at night making it easier for road users to see more clearly the road to be traversed, so as to improve traffic safety and security for road users and prevent the occurrence of accidents. crime, and gives an aesthetic value to a place. Public street lighting is an electronic item that is vulnerable or can be said to have a short service life, so repair and maintenance activities are absolutely necessary. Repairs can include network repairs, replacement of dead lights, checking cables and checking the condition of Public Street Lighting (PJU). The working system of street lights in Sei Kamah 1, Pasiran Village, Sei Dadap District, Asahan Regency, currently still uses the switch button on every electricity pole that is turned on by PLN officers or the surrounding community at night, and street lights still use essential light bulbs. so that the power released is too large and is detrimental to the electricity supplyer, although there are some street lights whose system turns on automatically when it is night and turns off automatically during the day but the installation is only in certain places plus sometimes street lights like this become the target of theft by irresponsible people. This study aims to create an automatic system street light design system in which this automatic system uses a motion sensor and a light sensor so that it can save more electric current. The device used is an arduino uno controller and uses the arduino ide programming language. The results of this study are expected to be a recommendation in the design of Public Street Lighting (PJU).